Pojok Baca Gen Cerdas: Membangun Generasi Cerdas Literasi dan Numerasi di SD Negeri 010 Kelurahan Tahtul Yaman Kecamatan Pelayangan Kota Jambi - Rully Andi Yaksa, Rully; Zulfikar, Muhammad; Amalianita, Berru; Niki Kusaini, Utami; Usmanto, Heri (Universitas PGRI Palembang, 2024)
This study aims to develop and implement the Pojok Baca (Reading Corner) program as an effort to enhance literacy and numeracy skills at SD Negeri 010, Tahtul Yaman Village, Pelayangan District, Jambi City. Based on initial observations conducted on March 27, 2024, several challenges were identified in student literacy and numeracy, such as low reading interest, limited library facilities, and a lack of support from parents and the community. To address these issues, Pojok Baca was designed in each classroom, providing books appropriate to the students' age levels. The implementation involved students, teachers, and parents in an interactive literacy process, utilizing games and songs to boost reading interest. Evaluation revealed that the program successfully increased students' reading interest and positively contributed to their literacy and numeracy skills. The program's success was supported by regular evaluations that provided feedback for further improvements and development. Thus, Pojok Baca has the potential to become an effective tool for fostering a literate and numerate generation in elementary schools.